Konsep Tathbîq dalam Pemikiran Hukum Islam - Mutopa Kamal (Istinbath | Jurnal Penelitian Hukum Islam, 2021)
This article attempts to describe and explore the dynamics of thought and the diversity of tathbîq Islamic law. The results of the search conducted by the author conclude that the dynamics of Islamic legal thought occurs because of the limitations of human ability to grasp the intent of Allah and His messenger. The results of this study indicate that the dynamics of Islamic legal thought occur because of the limited ability of humans to grasp the intentions of Allah and His Messenger. Therefore, continuous discussions need to be carried out in order to approach the ultimate truth and gain His pleasure. However, in history there have often been debates that tend to be unhealthy. Often appears in the debate, feeling that one's self is the best, feels that one's opinion is superior, and feels that one's sect or group is the most important. The results of this study recommend that Muslims channel their differences of opinion through mujâdalah bi al-ahsan in order to get Allah's pleasure in a tolerant frame. The diversity of legal tathbiq is an implication of the diversity of the mainstream and the internal perspectives of Muslims themselves.